Chemical encoding of amphiphilic copolymers for a dual controlled release from their assemblies. Issue 31 (22nd October 2014) - Lv, Li-Ping; Zhao, Yi; Landfester, Katharina; Crespy, Daniel
Abstract : Amphiphilic random copolymers are designed to bear a corrosion inhibitor as cleavable side group, which can be released upon activation by chemical reduction. Abstract : Amphiphilic random copolymers are designed to bear a corrosion inhibitor as cleavable side group, which can be released upon activation by chemical reduction. Polymer nanoparticles are obtained by self-assembly of the copolymers in water. A model dye is encapsulated in the nanoparticles and its release is triggered by reductive cleavage of the copolymer, leading hence to the co-release of the corrosion inhibitor. The present system has the advantage that the cleaved units are functional payloads.